العلاقة السببية بين رأس المال البشري والنمو الاقتصادي للعراق وعدد من دول الجوار العربي للفترة 1970 - 2010 - إبراهيم، أنوار سعيد (جامعة الأنبار - كلية الإدارة والاقتصاد, 2015)
أن لتراكم رأس المال البشري دور رئيسي في رفع الإنتاجية ومستويات الاستثمار والادخار والاستهلاك وتحسين حياة الإنسان سواء الأجيال الحاضرة أو القادمة من خلال ابتكار وتصنيع منتجات جديدة والمشاركة الفاعلة في النمو الاقتصادي، إذ يعمل التعليم والتدريب والتأهيل في رفع معدلات الناتج المحلي الإجمالي، وتقوم الدراسة في إطارها النظري على الدور الأساسي الذي يقوم رأس المال البشري وإمكانيته في تعزيز معدلات النمو الاقتصادي، وتم اختبار بيانات لمتوسط عدد سنوات الدراسة لقياس تراكم رأس المال البشري الذي يؤثر في معدلات النمو الاقتصادي، وقد تضمنت الدراسة قياس العلاقة السببية بين رأس المال البشري والنمو الاقتصادي للعراق وعدد من دول الجوار للمدة (1970-2010)، حيث تم أولاً: قياس متجه الانحدار الذاتي لتحديد قيمة التغيرات، فأشارت النتائج إلى وجود تأثير معنوي إيجابي ضعيف لمعادلة النمو الاقتصادي في دول العينة كافة، وثانياً: قياس اختبار العلاقة السببية لكرانجر للكشف عن اتجاه العلاقة بين متغيرات الأنموذج والتي تنشأ وفق أسس سببية، وبموجب ذلك أظهرت النتائج وجود علاقة سببية أحادية الاتجاه من تراكم رأس المال البشري إلى الناتج المحلي الإجمالي في الكويت، ووجود تأثير معنوي أحادي الاتجاه من الناتج المحلي الإجمالي إلى رأس المال البشري لباقي دول العينة وقدم البحث توصياته في رفع كفاءة الأيدي العاملة وقدرتها الإنتاجية، وتكييف نظم التدريب لتخلق عمالة قادرة على العمل وتحقيق التقدم التكنولوجي.
The accumulation human capital considered the base in raise productivity and levels of investment and savings and consumption,and improving human life , Through invetion and manufacture of new products and actively participate in economic growth whether present or future generations, and active participation in economic development , The study based on the theories framework in the basic role of Education and Training and its important role of the gross domestic product (GDP), This research trys to study the relationship between human capital and the economic growth among Iraq and number of neighbor countries for the period of (1970-2010), then we test the data for average study years as indicate for human capital that will be as expected effect on economic growth, Firstly measured vertical auto regression for definitive the value effect among the variables and Secondly, be test Granger Causality to find out the tread of relationship between variables model, those will grow up on causality reason, by used eviews program, the research provides that small significant positive impact of human capital on economic growth for all equation for the sample. Furthermore the test of Granger Causality shows that unidirectional effect from human capital to gross domestic product for Kuwait data, but other data shows unidirectional effect from gross domestic product to human capital for all equation for the sample,And Incraising the efficiency of labor and production capacity, and conditioning training systems to create employment able to work and achieve technological progress.
Keywords: العلاقة السببية -- رأس المال البشرى -- النمو الاقتصادي